Laparoscopic pediatric pyeloplasty using the Flexdex® articulating needle driver: step-by-step video. Issue 4 (August 2019) - Gorgen, A.R.H.; Araldi, M.; de Oliveira Paludo, A.; da Silva, A.G.T.; Ghissi, A.J.; Fernandes, A.S.; Tavares, P.; Rosito, T.E.; Cabral, R.D.
Summary: Ureteropelvic junction (UPJ) stenosis is the most common cause of pathological neonatal hydronephrosis. UPJ obstruction may be treated conservatively in some cases, but surgery is indicated if symptoms occur or renal function deteriorates. Pyeloplasty is the procedure of choice for UPJ stenosis. Pyeloplasty can be performed by open laparoscopic or robotic technique. The laparoscopic technique is safe and may be associated with shorter length of hospital stay and reduced complications. Lately, robotic pyeloplasty has been performed with similar results, adding the benefits of easier suturing maneuverability, but with increased costs. Flexdex® is a laparoscopic articulating needle driver that improves maneuverability and ergonomics. In this video, a laparoscopic pyeloplasty with the Flexdex® needle drive is described. The case was treated without any intraoperative complications and with no significant blood loss, and the patient was discharged the day after the procedure. After 90 days of follow-up, there were no complications reported.